STUDY OF HEMATOLOGICAL PARAMETERS OF RABBIT OFFSPRING SUBJECTED TO PRENATAL HYPOKINESIA - Hamidova, J.E.; Kazimov, A.H.; Aghayeva, E.N. (World of Medicine and Biology, 2025)
Changes in the blood parameters of newborn rabbit offspring whose prenatal development occurred under conditions of hypokinesia at various stages of pregnancy were explored. The changes in blood parameters were also observed to affect the viability of the offspring, depending on the pregnancy stage affected by hypokinesia. It was found that the embryonic stage is the most sensitive period, as the number of offspring born during this stage was lower compared to the control group. Based on our experiments, it can be stated that the most resilient stage in terms of offspring number is the fetal stage of pregnancy. The reproductive performance of female rabbits exposed to hypokinesia during this stage was similar to that of the control group and was approximately 90 %. It should be noted that the reduced viability of the newborn offspring is associated with profound changes in the vascular system of the “mother-fetus” system. Unlike pregnant rabbits that underwent gestation under normal conditions, newborns whose prenatal development occurred under hypokinetic conditions at different stages of pregnancy showed alterations in leukocyte formula parameters, platelet concentration, and erythrocyte sedimentation rate. The results of our research indicate that the investigation of erythrocyte and leukocyte formulas during pregnancy may be useful for implementing early preventive measures to mitigate the adverse effects of hypokinesia. These findings provide an important scientific foundation for studying the impact of restricted movement – hypokinesia – on reproductive health in space and for preserving the reproductive functions of animals and humans during future space missions.
Keywords: hipokinesia; embryo; pre-fetal growth; prenatal period